Effects of AminoGut and Diet Formulation Approach on Growth Performance and Economic Return in Nursery Pigs - M. A. Gonçalves; M. D. Tokach; S. S. Dritz; K. Touchette; J. M. DeRouchey; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
Diets containing animal protein sources have higher levels of glutamine than diets based on plant protein sources. Therefore, the objective of this study was to determine the effects of AminoGut (Ajinomoto Heartland, Inc., Chicago, IL) and protein source (animal vs. plant proteins) on growth performance and economic return in nursery pigs from 12 to 60 lb. AminoGut is a product that contains both glutamine and glutamate. A total of 1,134 pigs (337 × 1050; PIC, Hendersonville, TN, initially 11.6 ± 0.18 lb BW) were used in a 52-d trial. At the beginning of the experiment, pigs were weighed in pens, and pens were ranked by average BW and randomly assigned dietary treatments in a randomized complete block design based on BW. The treatment structure was a 2 × 3 factorial with 2 protein sources (animal vs. plant) and 3 AminoGut durations (0, 10, and 24 d). The experiment was divided into Phases 1 (d 0 to 10), 2 (d 10 to 24), and 3 (d 24 to 52). Pigs were fed a common diet during Phase 3. AminoGut was added at 0.8 and 0.6% in Phases 1 and 2, respectively. From d 0 to 10, pigs fed animal protein-based diet had marginally (P = 0.074) greater ADG and improved F/G (P = 0.035) compared to pigs fed plant-based diet. No evidence for differences was observed in pigs fed AminoGut in this phase (P>0.188). From d 10 to 24, pigs fed AminoGut had improved ADG (linear, P<0.022) and F/G (linear, P = 0.004). No evidence for differences was observed between protein sources in this phase. From d 24 to 52, pigs that had been previously fed AminoGut for 10 d had marginally improved F/G (quadratic, P = 0.057) compared to pigs not previously fed AminoGut or previously fed AminoGut for 24 d. No evidence for differences was observed between protein sources in this common phase. For the combined performance from Phases 1 and 2 (d 0 to 24), pigs fed AminoGut had improved ADG (linear, P<0.021), F/G (linear, P = 0.004), and BW (quadratic, P = 0.028) compared to pigs not fed AminoGut. No evidence for differences was observed between pigs fed different protein sources. For the overall performance (d 0 to 52), no statistical evidence for differences between pigs fed protein source or different AminoGut duration was observed. In conclusion, feeding AminoGut for 10 d post-weaning marginally improved growth performance until d 24 but there was no carry over effect when a common diet was fed from d 24 to 52. Further research should evaluate the supplementation of glutamine and glutamate throughout the nursery period and at greater inclusion levels.
Keywords: glutamate; glutamine; growth; nursery pig; protein source